Compressive strength-color change relationship in mortars subjected to high temperatures - Kizilkanat, Ahmet B.; Yuzer, Nabi (TURKISH CHAMBER CIVIL ENGINEERS, 2008)
In this study, the effects of high temperature and cooling regimes on the physical and mechanical properties of the mortar were observed. Mortar was made with siliceous and calcareous aggregates, CEM I 42.5, silica fume, fly ash and slag. Mineral admixtures replaced 10% cement by weight. These mortars were exposed to 100, 200, 300, 600, 900 and 1200 degrees C temperatures. Samples were cooled to room temperature in water and in air. Control tests were applied on these samples and Munsell Color System components hue, value and chroma were measured by spectrophotometer. Test results showed accordance between change of compressive strength and color of mortar which was exposed to high temperature. A relationship is established between compressive strength and the color change of mortar. Two separate formulas are drawn up based on different types of aggregate.
Keywords: FIRE-DAMAGED CONCRETE; Engineering